Role of Education Shaping in Professors of Islamic Boarding Schools in Indonesia - PURWANTO, MUHAMMAD ROY; MUKHARROM, TAMYIZ; CHOTIMAH, CHUSNUL; SANAKY, HUJAIR AH. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This paper attempts to describe the role of Islamic boarding school education (Pondok pesantren) in shaping the inclusive mentality and religious ideology of the community, especially in university professors. The results of the study show that teachers with experience in Islamic boarding schools have an inclusive religious ideology. The data shows that 95% of these teachers recognize the reality outside of schools and groups. Eighty percent are tolerant in religion or practice fiqh. Sixty-five percent do not agree with the khilafah, and thirty percent believe that it is difficult to implement the khilafah in Indonesia. RESUMEN Este documento intenta describir el papel de la educación de los internados islámicos (Pondok pesantren) en la configuración de la mentalidad inclusiva y la ideología religiosa de la comunidad, especialmente en los profesores universitarios. Los resultados del estudio muestran que los profesores que tienen experiencia en internados islámicos poseen una ideología religiosa inclusiva. Los datos muestran que el 95% de estos docentes reconocen la realidad fuera de las escuelas y grupos. El ochenta por ciento son tolerantes en la religión o practican el fiqh. El sesenta y cinco por ciento no está de acuerdo con la khilafah, y el treinta por ciento cree que es difícil implementar la khilafah en Indonesia.